Effect of natural enemies on the invasion of the exotic plant buffalobur (Solanum rostratum Dunal.) in the arid oasis of Urumqi - Jian-Xiao, He; Yimingniyazi, Amanula (Frontiers in Environmental Science, 2023)
Studying the interspecific relationships of exotic species can provide an important theoretical basis for revealing the invasion processes of exotic species, predicting the scope and harm of proliferation, and, subsequently, suggesting reasonable prevention and control measures. Buffalobur (Solanum rostratum Dunal.) is a typical alien invasive plant that causes significant harm in the oasis of the arid region of Xinjiang, being primarily distributed on both sides of the Toutun River and irrigated farmland. Parasitic dodders (Cuscuta australis R. Br.), in addition to phytophagous insects, such as potato beetles (Leptinotarsa decemlineata (Say)), and cotton bollworms (Helicoverpa armigera (Hubner)), that fed on the buffalobur plant were observed to be distributed in the field. In order to explore the impact of dodder parasitism and insect feeding on buffalobur invasion, buffalobur was selected as the main research material in this study. The effects of different degrees of parasitism (non-parasitism, mild parasitism, and severe parasitism), different stages of parasitism (non-parasitism, seedling parasitism, flowering parasitism, and fruit parasitism), and different levels of simulated insect feeding (non-parasitism, mild feeding, moderate feeding, and severe feeding) on the growth, development, and competitiveness of buffalobur were studied. The results showed that parasitism from dodders and feeding by phytophagous insects significantly reduced the biomass of buffalobur (p < 0.05), thus inhibiting its growth and development. In addition, the root–shoot ratio of the buffalobur was increased, which influenced its growth–defense strategy. At different degrees of parasitism from dodders and different degrees of feeding by phytophagous insects, the biomass of the buffalobur was decreased. However, parasitism from dodders at different stages reduced the biomass and competitive ability of buffalobur (p < 0.05). Considering that the dodders and phytophagous insects could parasitize and feed not only on buffalobur but also on other crops, they cannot be used for the control of buffalobur.